2011
DOI: 10.1074/jbc.m110.206714
|View full text |Cite
|
Sign up to set email alerts
|

Hair Follicular Expression and Function of Group X Secreted Phospholipase A2 in Mouse Skin

Abstract: Although perturbed lipid metabolism can often lead to skin abnormality, the role of phospholipase A 2 (PLA 2 ) in skin homeostasis is poorly understood. In the present study we found that group X-secreted PLA 2 (sPLA 2 -X) was expressed in the outermost epithelium of hair follicles in synchrony with the anagen phase of hair cycling. Transgenic mice overexpressing sPLA 2 -X (PLA2G10-Tg) displayed alopecia, which was accompanied by hair follicle distortion with reduced expression of genes related to hair develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 81 publications
1
49
0
Order By: Relevance
“…Notably, sPLA 2 -IIE is located in these affected regions (the innermost IRS layer and the companion layer along growing hairs) within hair follicles, lending further support to the idea that sPLA 2 -IIE regulates hair follicle homeostasis at these restricted locations. We previously reported that Pla2g10-transgenic mice displayed alopecia with perturbed hair cycling and that Pla2g10 Ϫ/Ϫ mice showed ORS hypoplasia (21). However, the very low expression of endogenous sPLA 2 -X in mouse skin argues against its hair follicle-intrinsic role.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, sPLA 2 -IIE is located in these affected regions (the innermost IRS layer and the companion layer along growing hairs) within hair follicles, lending further support to the idea that sPLA 2 -IIE regulates hair follicle homeostasis at these restricted locations. We previously reported that Pla2g10-transgenic mice displayed alopecia with perturbed hair cycling and that Pla2g10 Ϫ/Ϫ mice showed ORS hypoplasia (21). However, the very low expression of endogenous sPLA 2 -X in mouse skin argues against its hair follicle-intrinsic role.…”
Section: Discussionmentioning
confidence: 99%
“…This action of sPLA 2 -IIF as an "epidermal sPLA 2 " depends at least in part on the generation of plasmalogen lysophosphatidylethanolamine (P-LPE; lysoplasmalogen), a unique lysophospholipid that can promote keratinocyte activation and epidermal hyperplasia. Beyond sPLA 2 -IIF, transgenic overexpression of sPLA 2 -IIA or -X causes alopecia and epidermal hyperplasia (20,21), although endogenous expression of these two sPLA 2 s as well as sPLA 2 -IB, -IID, and -V in mouse skin is low or almost undetectable (19). sPLA 2 -IIE is an isoform structurally most homologous to sPLA 2 -IIA (22,23).…”
mentioning
confidence: 99%
“…In cases such as this, transgenic mice are useful when searching for lipidmetabolic processes driven by a particular sPLA 2 in vivo, because lipid mobilization in the transgenic mice is typically prominent and easy to chase using a lipidomics approach. Another noteworthy issue is that the overall phenotypes of mice transgenic for different sPLA 2 s are not entirely identical (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). If different sPLA 2 s have similar enzymatic properties, then the output phenotypes of mice transgenic for them should be similar.…”
Section: S Participate In Diverse Biologicalmentioning
confidence: 99%
“…LPC is a candidate product responsible for the action of sPLA 2 -X, because it can partially restore the defective fertilization of wild-type sperm treated with anti-sPLA 2 -X antibody ( 132 ). Lastly, a striking skin phenotype characterized by alopecia in Pla2g10 -transgenic mice points to a unique role of sPLA 2 -X in hair homeostasis ( 36 ). Although the coat hairs of Pla2g10 Ϫ / Ϫ mice appear grossly normal, they have ultrastructural abnormalities including a hypoplasic outer root sheath and reduced melanin granules in their hair follicles.…”
Section: Pla2g12/spla 2 -Xii Subfamilymentioning
confidence: 99%
“…Some of the biological actions of sPLA 2 s in vivo have been investigated using sPLA 2 -overexpressing transgenic mice (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). However, the results should be interpreted with caution, as a super-physiological level of sPLA 2 , even in tissues or cells where the enzyme is not intrinsically expressed, could result in an artifi cial phenotype.…”
Section: S Participate In Diverse Biologicalmentioning
confidence: 99%